EFFECT OF GIVING LAMTORO LEAF JUICE (LEUCAENA LEUCOCEPHALA) THROUGH DRINKING WATER ON THE PHYSICAL COMPOSITION OF MALE BALI DUCK CARCASSES - N. G. A. P. D. V., Sari; Siti, N.W.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the effect of giving lamtoro leaf juice on the physical composition of male Balinese duck carcasses. This research was conducted at Farm Sesetan, Faculty of Animal Husbandry, Udayana University for 8 weeks. The design used was a complete randomized plan (RAL) with 4 treatments, 4 repetitions, and each repetition contained 3 ducks. The treatment given to Balinese ducks in the form of lamtoro leaf juice in drinking water is: (P0) drinking water without lamtoro leaf juice, (P1) drinking water with 2% lamtoro leaf juice, (P2) drinking water with 4% lamtoro leaf juice, and (P3) drinking water with 6% lamtoro leaf juice. The variables observed were cutting weight, carcass weight, carcass percentage, and carcass physical composition. The results of this study showed that the percentage of carcasses of male Balinese ducks given 2% and 4% lamtoro leaf juice in drinking water tended to be higher than the control (P0) and in the P3 treatment was lower than the control. Giving lamtoro leaf juice in P1, P2, and P3 treatment can increase the percentage of male Bali duck bones. The percentage of meat in P1, P2, and P3 treatments tended to be higher than the control (P0). The percentage of subcutaneous fat including skin tended to be lower than the control (P0). From the results of this study it can be concluded that giving lamtoro leaf juice in drinking water as much as 2-6% can increase bone percentage, but tends to increase the percentage of carcass and meat percentage and decrease the percentage of subcutaneous fat including skin.